Prácticas literarias de pertenencia: identificación y diferenciación cultural en la loa del Divino Narciso de Juana Inés de la Cruz - Jünke, Claudia (iMex. México Interdisciplinario / Interdisciplinary Mexico, 2019)
The article investigates the transcultural exchanges and the traces of a creole consciousness in the loa of the auto sacramental El Divino Narciso by Juana Inés de la Cruz. Our reading of this allegorical play takes the concept of belonging as a tool for the analysis of the multifaceted dynamics of cultural identification and differentiation that are deployed in this literary text from the Mexican colonial baroque of the 17th century. We will focus on three dimensions on which the author introduces differentiations that structure the topic and the action of the play: the geocultural dimension, the ethic dimension and the geopolitical dimension. In doing so, we propose to consider Juana’s creole consciousness not so much as an identity that she possesses but rather as the totality of the complex and sometimes contradictory practices of belonging that are expressed in her texts.
Keywords: 860 Spanish & Portuguese literatures; literatura mexicana; Mexican Literature; Juana Inés de la Cruz; belonging; creole identity; loa of Divino Narciso; New Spain